LEGAL SYSTEM OF FINLAND - Kobko-Odariy , Viktoria (Collection of scientific papers «ΛΌГOΣ», 2025)
The law of Finland is related to Scandinavian law and is particularly close to the law of Sweden. There is much similarity in the law of the Nordic countries, not only because of the geo-physical proximity of these countries and their historical and political development, but also because of the deliberate legal harmonisation policies pursued in these countries. The result of this difficulty is that many of the legal norms (individual norms and even legal institutions), especially in the area of private law, are the same in all Scandinavian countries.